Evidence on the Porter hypothesis: China’s Resource Tax Law may be a path to achieve corporate sustainable development - Xiaoqi Zhang; Yu He (PLoS ONE, 2025)
Promoting utilization efficiency and sustainable energy development is crucial for achieving sustainable social development in China, the largest energy producer and consumer worldwide. Accordingly, the Chinese authorities enacted the Resource Tax Law (RTL) on August 26, 2019. Whether such a policy can achieve its desired goals has not been verified. Thus, our study applies a difference-in-differences approach to examine the effect of RTL on a firm’s energy efficiency (EE) with panel data of A-shares from 2017 to 2022. Benchmark analysis and robustness tests demonstrate RTL’s significant effect on resource-based firm’s EE. Additional tests deeply explore the policy effect under different situations. First, RTL boosts more for firms with higher initial EE levels than those with lower levels. Second, RTL enhances EE by promoting firms’ research and development investments, confirming the existence of the Porter hypothesis in China. Third, this policy shows a stronger positive effect on firms with political connections than those without. Finally, we detect that RTL has no significant impact in the western region, while its effect is significantly stronger in the middle region compared to the eastern region. Our empirical findings suggest that corporate firms and the government should adopt appropriate actions to enhance RTL’s policy effect.